1993
DOI: 10.1016/0014-5793(93)81681-o
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of type VI collagen genes in drug‐induced gingival enlargement

Abstract: Fibrotic gingival enlargements induced by phenytoin or nifedipine were examined with special reference to type VI collagen expression. Immunolocalization studies showed abnormal accumulation of type VI collagen around the collagen fiber bundles in the fibrotic gingival enlargements. Examination of total RNA extracted from fibroblasts and tissues of enlarged gingivae demonstrated increased type VI collagen steady-state mRNA levels. These results suggest that excessive deposition of type VI collagen in drug-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…However, whether this excess matrix accumulation can be solely attributed to the effects of nifedipine and phenytoin alone has been unclear. In gingival tissues isolated from patients diagnosed with nifedipine and phenytoin DIGE, increased pSMAD2/3 nuclear translocation, periostin and fibronectin immunoreactivity, as well as increased collagen density were evident compared to gingiva from healthy individuals confirming previous studies (Takagi et al 1991; Shikata et al 1993; Pisoschi et al 2014). Although only qualitative, staining levels for fibronectin, periostin as well as collagen density seemed higher in phenytoin DIGE compared to nifedipine, which is supported by previous research that phenytoin results in a more fibrotic lesion (Uzel et al 2001).…”
Section: Discussionsupporting
confidence: 86%
“…However, whether this excess matrix accumulation can be solely attributed to the effects of nifedipine and phenytoin alone has been unclear. In gingival tissues isolated from patients diagnosed with nifedipine and phenytoin DIGE, increased pSMAD2/3 nuclear translocation, periostin and fibronectin immunoreactivity, as well as increased collagen density were evident compared to gingiva from healthy individuals confirming previous studies (Takagi et al 1991; Shikata et al 1993; Pisoschi et al 2014). Although only qualitative, staining levels for fibronectin, periostin as well as collagen density seemed higher in phenytoin DIGE compared to nifedipine, which is supported by previous research that phenytoin results in a more fibrotic lesion (Uzel et al 2001).…”
Section: Discussionsupporting
confidence: 86%
“…That study suggested that 10 −7 m nifedipine significantly increased the net deposition of both collagenous and non‐collagenous proteins within the extracellular matrix by fibroblasts derived from normal gingiva following exposure to 10 −7 m nifedipine (29). The mechanism for the altered collagen metabolism possibly involves the effects of nifedipine on collagen gene expression in gingival fibroblasts (30, 31).…”
mentioning
confidence: 99%
“…Recent evidence suggests that 10 ª7 M nifedipine significantly increases deposition of both collagenous and noncollagenous proteins into the extracellular matrix by fibroblasts derived from normal gingiva following exposure to 10 ª7 M nifedipine (24). Nifedipine appears to affect collagen gene expression selectively, as mRNA for type I collagen has been reported to be decreased (25), while mRNA for type IV collagen was increased coincident to exposure of gingival fibroblasts to nifedipine (26).The effect of IL-1 on collagen deposition by fibroblasts into the extracellular matrix is controversial, since reports of increased (27)(28)(29)(30)(31) or decreased (21,32) collagen synthesis coincident to exposure to IL-1 are available. In addition, IL-1 also inhibits collagen accumulation within tissues (33) by stimulation of matrix metalloproteinase expression (34).…”
mentioning
confidence: 99%